NO-Dependent Mechanisms of Myosin Heavy Chain Transcription Regulation in Rat Soleus Muscle After 7-Days Hindlimb Unloading - Sharlo, Kristina A.; Paramonova, Inna I.; Lvova, Irina D.; Vilchinskaya, Natalia A.; Bugrova, Anna E.; Shevchenko, Tatiana F.; Kalamkarov, Grigoriy R.; Shenkman, Boris S. (Frontiers in Physiology, 2020)
It is known that nitric oxide may affect myosin heavy chain isoforms (MyHCs) mRNA transcription in skeletal muscles. The content of nitric oxide in soleus muscles decreases during rat hindlimb unloading as well as slow MyHC mRNA transcription. We aimed to detect which signaling pathways are involved in nitric oxide-dependent prevention of hindlimb-suspension (HS)-induced changes in MyHCs expression pattern. Male Wistar rats were divided into four groups: cage control group (C), hindlimb suspended for 7 days (7HS), hindlimb suspended for 7 days with L-arginine administration (7HS+A) (500 mg/kg body mass) and hindlimb suspended for 7 days with both L-arginine (500 mg/kg) and NO-synthase inhibitor L-NAME administration (50 mg/kg) (7HS+A+N).L-arginine treatment during 7 days of rat HS prevented hindlimb suspension-induced NO content decrease and slow MyHC mRNA transcription decrease and attenuated fast MyHC IIb mRNA transcription increase; it also prevented NFATc1 nuclear content decrease, calsarcin-2 expression increase and GSK-3β Ser 9 phosphorylation decrease. Moreover, L-arginine administration prevented the hindlimb suspension-induced myh7b and PGC1α mRNAs content decreases and slow-type genes repressor SOX6 mRNA transcription increase. All these slow fiber-type protective effects of L-arginine were blocked in HS+A+N group, indicating that these effects were NO-dependent. Thus, NO decrease prevention during hindlimb suspension restores calcineurin/NFATc1 and myh7b/SOX6 signaling.